Bank loan maturity and corporate investment - İbrahim Yarba; Burak Deniz (Central Bank Review)
This study analyzes bank loan maturity and corporate investment linkage by using novel firm-level data covering the universe of all incorporated firms in Türkiye over the last decade. The results of the panel regression model with multi-dimensional fixed effects reveal that loan maturity has a significant positive association with investment, indicating that longer debt maturity fosters corporate investment. The results reveal that the positive linkage between longer debt maturity and investment is more pronounced for small and medium-sized enterprises (SMEs). This is also the case for young firms and firms with high growth opportunities. Considering the evidence provided in the literature that bank lending conditions, including maturity structure, are highly cyclical and vulnerable to financial conditions and economic policy uncertainties, our findings highlight the importance of reducing the policy uncertainties as well as the importance of policies that make equity financing more attractive and deepen the capital markets.